2016
DOI: 10.1038/nm.4017
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII is a RIP3 substrate mediating ischemia- and oxidative stress–induced myocardial necroptosis

Abstract: Regulated necrosis (necroptosis) and apoptosis are crucially involved in severe cardiac pathological conditions, including myocardial infarction, ischemia-reperfusion injury and heart failure. Whereas apoptotic signaling is well defined, the mechanisms that underlie cardiomyocyte necroptosis remain elusive. Here we show that receptor-interacting protein 3 (RIP3) triggers myocardial necroptosis, in addition to apoptosis and inflammation, through activation of Ca(2+)-calmodulin-dependent protein kinase (CaMKII) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
648
6
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(704 citation statements)
references
References 57 publications
36
648
6
14
Order By: Relevance
“…Pertinent to the present study, necroptosis has been recognized as a key cell death pathway in cardiomyocytes during ischemia-reperfusion injury and acute coronary syndromes (24)(25)(26).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Pertinent to the present study, necroptosis has been recognized as a key cell death pathway in cardiomyocytes during ischemia-reperfusion injury and acute coronary syndromes (24)(25)(26).…”
Section: Introductionsupporting
confidence: 53%
“…Cardiomyocytes have been shown to die by apoptosis or necroptosis during injury or disease (24)(25)(26). Apoptosis is an immunoquiescent form of cell death that requires the activity of cysteine proteases known as caspases (42).…”
Section: Discussionmentioning
confidence: 99%
“…RIP3 co‐localized with mitochondria when necrosis was induced in a kinase activity‐dependent manner and promoted mitochondrial metabolism and ROS production by activating the PYGL, GLUL and GLUD1, leading to the consequent necrosis as mentioned above (Figures 3 and 4). 60 In a recent study, Ting Zhang et al found that siRNA‐mediated knockdown of Cypd markedly alleviated RIP3‐induced cardiomyocyte necrosis as assessed by cellular ATP content and LDH release, further revealing the close relationship between these 2 pathways 61…”
Section: Signalling Interactionmentioning
confidence: 98%
“…Reactive oxygen species (ROS) promote necroptosis in cardiomyocytes, liver cells, Jurkat cells and lung adenoma cells (13)(14)(15)(16). However, the effect of ROS on the necroptosis of renal tubular epithelium remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified necroptosis in ATN induced by various stimuli, including ischemia/reperfusion, contrast medium and cisplatin (10-12). RIP-1 inhibition by necrostatin-1 (Nec-1), or knockout of RIP-3 or MLKL all prevent ATN (10-12).Reactive oxygen species (ROS) promote necroptosis in cardiomyocytes, liver cells, Jurkat cells and lung adenoma cells (13)(14)(15)(16). However, the effect of ROS on the necroptosis of renal tubular epithelium remains unknown.…”
mentioning
confidence: 99%